2011
DOI: 10.1111/j.1365-2656.2011.01891.x
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of avian natal dispersal distance provides prior information for investigating response to landscape change

Abstract: Summary1. Informative Bayesian priors can improve the precision of estimates in ecological studies or estimate parameters for which little or no information is available. While Bayesian analyses are becoming more popular in ecology, the use of strongly informative priors remains rare, perhaps because examples of informative priors are not readily available in the published literature. 2. Dispersal distance is an important ecological parameter, but is difficult to measure and estimates are scarce. General model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 51 publications
1
72
1
Order By: Relevance
“…Our comparative tests support the prediction that sex-biased dispersal is related to body size [9,10,12]. Specifically, we find that larger species have more male-biased dispersal, that distance is increasing more rapidly in males than in females, and that female and male distances are both positively correlated with their sex-specific masses (Tables 1 and 2; Figure 1; Supplemental Table 3).…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Our comparative tests support the prediction that sex-biased dispersal is related to body size [9,10,12]. Specifically, we find that larger species have more male-biased dispersal, that distance is increasing more rapidly in males than in females, and that female and male distances are both positively correlated with their sex-specific masses (Tables 1 and 2; Figure 1; Supplemental Table 3).…”
Section: Discussionsupporting
confidence: 65%
“…Conversely, previous studies of species-specific dispersal have focused instead on the potential effects of other life history traits such as body size and territory area [9][10][11]. In particular, prior species-specific investigations have found that the natal dispersal distances (hereafter, referred to as distances) of a group are positively correlated with body size [12,13]. In animals, one explanation for this positive correlation is that the mass-specific energy cost of transport (COT) decreases with body size, thereby making it relatively cheaper for larger species to move farther [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations